2016
DOI: 10.1007/s12253-016-0094-1
|View full text |Cite
|
Sign up to set email alerts
|

The Value of a Novel Panel of Cervical Cancer Biomarkers for Triage of HPV Positive Patients and for Detecting Disease Progression

Abstract: In the era of primary vaccination against HPV and at the beginning of the low prevalence of cervical lesions, introduction of screening methods that can distinguish between low- and high-grade lesions is necessary in order to maintain the positive predictive value of screening. This case-control study included 562 women who attended cervical screening or were referred for colposcopy and 140 disease free controls, confirmed by histology and/or cytology. The cases were stratified by age. Using routine exfoliated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Moreover, TP63 and its position at 3q28 were observed as frequent HPV integration spots in both cervical cancers and oropharyngeal squamous cell carcinomas [9], [35], [36]. Over-expression of ΔNp63 was reported in cervical cancer and is useful for differentiating cervical lesion severity [15], [37]. Based on these findings, we chose ΔNp63 as a potential biomarker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, TP63 and its position at 3q28 were observed as frequent HPV integration spots in both cervical cancers and oropharyngeal squamous cell carcinomas [9], [35], [36]. Over-expression of ΔNp63 was reported in cervical cancer and is useful for differentiating cervical lesion severity [15], [37]. Based on these findings, we chose ΔNp63 as a potential biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical researches have been conducted to improve cervical cancer screening strategies. Because HPV is necessary but not the only determining factor in the progression to cervical cancer, an increasing number of screening methods have begun to focus on molecular alterations during tumorigenesis [11], [12], [13], [14], [15]. For instance, p16/Ki67 and microRNAs have been reported as promising for improving the sensitivity and specificity of HPV-positive triage effects [14], [16].…”
Section: Discussionmentioning
confidence: 99%
“…Of clinical relevance, edelfosine, a glycerophospholipid with antitumoral properties that inhibits SK3 channel activity, can inhibit migration and invasion of cancer cells in vitro and in vivo in an SK3-dependent manner, pointing towards a possible use of edelfosine in prostate cancer treatment [ 51 54 ]. Although KRT78 has not previously been associated with prostate cancer, it has been identified as a diagnostic marker for metastatic melanoma [ 55 ] and cervical cancers [ 56 ]. Investigation of the function of other GWAS-identified CTCF sites involved in chromatin loops may reveal additional genes involved in the development or diagnosis of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In cervical cancer, the high expression of DSG2 was associated with HPV-positive status [160], suggesting that DSG2 may be involved in HPV-induced cervical carcinogenesis. Varga et al [161] revealed that DSG3, as one of prognostic panel genes, has the ability to differentiate high-risk HPV-positive CIN1 (cervical intraepithelial neoplasia) and cancer cases. E6 and E7 early gene products contribute to the oncogenic potential of high-risk HPV [162].…”
Section: Discussionmentioning
confidence: 99%